牛顿的广义二项式定理---微积分推倒的开始

数学与算法 专栏收录该内容
4 篇文章 1 订阅

Theorem

Let  αR  be a real number.

Let  xR  be a real number such that  |x|<1 .


Then:

(1+x)α=n=0αnn!xn=n=01n!(k=0n1(αk))xn

where  αn  denotes the falling factorial.


That is:

(1+x)α=1+αx+α(α1)2!x2+α(α1)(α2)3!x3+


Proof

Let  R  be the radius of convergence of the power series:

f(x)=n=0k=0n1(αk)n!xn

By Radius of Convergence from Limit of Sequence:

1R=limn|α(α1)(αn)|(n+1)!n!|α(α1)(αn+1)|
  1R = limn|α(α1)(αn)|(n+1)!n!|α(α1)(αn+1)|   
  = limn|αn|n+1   
  = 1   

Thus for  |x|<1 Power Series Differentiable on Interval of Convergence applies:

Dxf(x)=n=1k=0n1(αk)n!nxn1


This leads to:

  (1+x)Dxf(x) = n=1k=0n1(αk)(n1)!xn1+n=1k=0n1(αk)(n1)!xn   
  = α+n=1k=0n(αk)n!+k=0n1(αk)(n1)!xn   
  = α+n=1k=0n(αk)(n1)!(1n+1αn)xn   
  = α+n=1k=0n(αk)(n1)! αn(αn)xn   
  = α1+n=1k=0n1(αk)n!xn   
  = αf(x)   

Gathering up:

(1+x)Dxf(x)=αf(x)

Thus:

Dx(f(x)(1+x)α)=α(1+x)α1f(x)+(1+x)αDxf(x)=0

So  f(x)=c(1+x)α  when  |x|<1  for some constant  c .

But  f(0)=1  and hence  c=1 .


Historical Note

The General Binomial Theorem was announced by Isaac Newton in 1676.

However, he had no real proof.

Euler made an incomplete attempt in 1774, but the full proof had to wait for Gauss to provide it in 1812.

牛顿提出了广义二项式定理,并以此为基础发明了微积分的方法,但对于二项式定理没有给出证明,欧拉尝试过,但失败了,直到1812年高斯利用微分方法得到了证明!


  • 1
    点赞
  • 0
    评论
  • 0
    收藏
  • 一键三连
    一键三连
  • 扫一扫,分享海报

©️2021 CSDN 皮肤主题: 大白 设计师:CSDN官方博客 返回首页
实付
使用余额支付
点击重新获取
扫码支付
钱包余额 0

抵扣说明:

1.余额是钱包充值的虚拟货币,按照1:1的比例进行支付金额的抵扣。
2.余额无法直接购买下载,可以购买VIP、C币套餐、付费专栏及课程。

余额充值